The Effectiveness of Baby Massage on Weight Gain and Sleep Quality of Babies Aged 3-6 Months at the Main Clinic of Rufaidah Care Banda Aceh City - Syarifah Maulida; Desi Nanda Sari; Ira Yulianti; Dhita Meuthia Sari; Devi Arisandi (Journal Public Health and Clinical Science, 2026)
Every baby experiences stages of growth and development in his or her lifetime. Growth and development is a continuous process, and growth is part of the developmental process, one of which is weight and sleep quality, many babies have sleep problems in Indonesia, which is around 44.2%. To determine the effectiveness of baby massage on weight gain and sleep quality of babies aged 3-6 months at the Rufaidah Care Main Clinic, Banda Aceh City Research Design. This study is a quasi-experimental research without a control group with a design one group pretest post test. This design uses one group of samples by taking one measurement before the treatment and after that another measurement is taken (post test). The population in this study is all babies aged 3-6 months as many as 27 people, the sampling technique is Total Sampling with a total sample of 27 people using the Paired t-test. that the application of Baby Massage was effective on weight gain and sleep quality because indigo p Value 0.00 (p< 0.05). Conclusion: Based on the results of the tests that have been carried out, it can be concluded that there is an effectiveness of baby massage.